Evaluation of the review models and approval timelines of authorities participating in the East African Medicine Regulatory Harmonisation initiative: alignment and strategies for moving forward - Ngum, Nancy; Ndomondo-Sigonda, Margareth; Habonimana, Rémy; Siyoi, Fred; Irasabwa, Clarisse; Ojukwu, Julia; Apolinary, Felchism; Okello, Andrew; Ahmada, Sabrina; Walker, Stuart; Salek, Sam (Frontiers in Medicine, 2024)
Introduction: Medicines regulatory harmonisation has been embraced by many national regulatory authorities (NRAs) to improve public health through faster availability of safe, high-quality, and effective medical products to patients and enhanced standardisation of technical guidelines and work sharing, leading to reduced cost to pharmaceutical companies.After ten years of implementing regulatory harmonisation by the East African Community Medicines Registration Harmonization (EAC-MHR) initiative, it is now imperative for participating NRAs to rely on each other to minimise duplication of use of limited resources.Major challenges in implementing reliance are the lack of clear registration processes and delays in the approval. The aim of this study was to compare review models, target timelines and data requirements used in assessing applications by EAC-MRH NRAs so as to align and propose strategies for improvement.Methods: A validated questionnaire that standardises and captures review processes was completed by the head of the medicine's registration division in each of the seven EAC-MRH NRAs. A country report based on the completed questionnaire was developed for each NRA and validated by the heads of the respective authorities.Results: Most applications received by all countries were for generics except Kenya, which received a significant number of new active substance applications (55 and 53 in 2020 and 2021). Mean approval times for generics using full review varied, with Tanzania's time declining for the three years. Target timelines for full review for the five countries ranged between 180 calendar days (Tanzania) to the highest 330 days (Zanzibar). The three countries (Kenya, Rwanda and Uganda) utilising the verification review model had a target timeline of 90 days. All six authorities conducted abridged reviews and fast-track assessments through a priority review track. The common technical document format was mandatory for applications in all authorities. The target timeline for key milestones in the review process varied for each country with a few similarities.The study has provided a baseline for review models, target timelines and data requirements utilised in assessing applications for registration by EAC-MRH NRAs.Implementing the recommendations from this study will enable the NRAs to align and improve their registration processes.